2023
DOI: 10.2147/idr.s410374
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Anticoagulant Therapy in COVID-19 Patients with Pre-Existing Cardiovascular Diseases: A Systematic Review

Abstract: The COVID-19 infection caused by SARS-CoV-2 is a healthcare crisis that has led to unparalleled disruption and has impacted healthcare services, leading to significant morbidity and mortality in the worldwide population. Insufficient data on the management of COVID-19 complications such as hypercoagulability and the controversy about the benefits of anticoagulant therapy are major challenges encountered by clinicians, especially for patients with pre-existing cardiovascular diseases (CVD), and are still debata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…Thus, anticoagulants have been primarily ordered for severe COVID-19 patient treatment. However, information on the prognosis of COVID-19 patients with concomitant CV disease regularly using anticoagulants is still debatable, and more evidence are needed to investigate the valuable outcomes of the use of anticoagulants in these patients [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] . The association of systemic anticoagulation with extended survival of hospitalized patients with COVID-19 demonstrated no statistical significance according to a previous cohort study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, anticoagulants have been primarily ordered for severe COVID-19 patient treatment. However, information on the prognosis of COVID-19 patients with concomitant CV disease regularly using anticoagulants is still debatable, and more evidence are needed to investigate the valuable outcomes of the use of anticoagulants in these patients [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] . The association of systemic anticoagulation with extended survival of hospitalized patients with COVID-19 demonstrated no statistical significance according to a previous cohort study.…”
Section: Discussionmentioning
confidence: 99%
“…And we found that prophylactic anticoagulation therapy during hospitalization in this population was effective for the prevention from MACEs during the long-term follow-up after discharge. If anticoagulants are to be used, DOACs are favored due to their better action and lesser side effects compared with other anticoagulant agents such as VKAs [15] . Further research is required to describe the best course and optimal dose of anticoagulant use in the treatment of patients with COVID-19 with comorbidities such as CV disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation